Actinobacterial Diversity in the Sediments of Five Cold Springs on the Qinghai-Tibet Plateau - Yang, Jian; Li, Xiaoyan; Huang, Liuqin; Jiang, Hongchen (Frontiers in Microbiology, 2015)
The actinobacterial diversity was investigated in the sediments of five cold springs in Wuli region on the Qinghai-Tibet Plateau using 16S rRNA gene phylogenetic analysis. The actinobacterial communities of the studied cold springs were diverse and the obtained actinobacterial operational taxonomic units (OTUs) were classified into twelve actinobacterial orders (e.g. Acidimicrobiales, Corynebacteriales, Gaiellales, Geodermatophilales, Jiangellales, Kineosporiales, Micromonosporales, Micrococcales, Nakamurellales, Propionibacteriales, Pseudonocardiales, Streptomycetales) and unclassified Actinobacteria. The actinobacterial composition varied among the investigated cold springs and were significantly correlated (r = 0.748, P = 0.021) to environmental variables. The actinobacterial communities in the cold springs were more diverse than other cold habitats on the Tibetan Plateau, and their compositions showed unique geographical distribution characteristics. Statistical analyses showed that biogeographical isolation and unique environmental conditions might be major factors influencing actinobacterial distribution among the investigated cold springs.